POSISI PEREMPUAN DALAM PROSESI PENGUBURAN MAYAT DAN PENGABENAN DI DESA ADAT TERUNYAN KECAMATAN KINTAMANI KABUPATEN BANGLI - I Putu Dibya Wisnawa Putra (Universitas Pendidikan Ganesha, 2013)
﻿ABSTRACThis study aims to find out: 1) the foundation fhilosofi of banning women participated in the procession to the cemetery burial and cremation Village district of Kintamani district Terunyan Bangli, 2) the position of women in the procession and burial cremtion at the traditional vilage Terunyan Kintamani district Bangli, 3) what values are to be maintained rohibiting women participate to the grave in the burial procession and cremation in the traditional village Terunyan Kintamani district Bangli. The research was conducted in the Terunyan village of Kintamani district Bangli, that the object of study is the position of women in the procession and cremation burials bodies. This research is a qualitative descriptive research methods with empirical approach. Data collection techniques to perform interviews, document recording and observation techniques. Technique of determining sample with engineering purposive sampling the technique is done with a specific purpose. Data processing techniques with a qualitative descriptive analysis techniques the authors attempted describe the data that have been collected in a systematic then analyze it, so it can be concluded in general are accompanied by arguments. The results showed that: 1) foundation filosophy of prohibiting women participate to the grave in the burial procession and cremation is a public trust that meraga istri who holds Ida Ratu Ayu Dalem Pingit and the presence of an inscription in the form temaga, 2) the position of women in the procession and cremation burial pradana remain as obligations like a woman and be a major helper, 3) values to be maintained prohibiting women participate in the procession to the cemetery of burial and cremation in the traditional Terunyan village of Kintamani district Bangli including : a) religious values or beliefs of the worshiping ida Betara meraga istri and the existence of a inscription the form temaga, b) cultural values of gender Potition and cultural mores are owned by the Terunyan village, c) value of advice pengelingsir believed to be hereditary and, d) concept value solidarity, segilik seguluk sebayantaka.Keywords: Women, Procession Burial Bodies and Cremation